Pengaruh Model Pembelajaran Inkuiri Terbimbing dengan Mind Map & Kooperatif Tipe Tgt terhadap Pemahaman Konsep Siswa - Saridewi, Maria Paulin (BIO-EDU: Jurnal Pendidikan Biologi, 2019)
21st-century learning emphasizes the concept of student-centered learning, so that learning is more meaningful for students, because students are required not only to do the task but also to understand important concepts. However, the problem now faced is the still low understanding of students' concepts. One reason is the teacher teaching method that is still conventional. The learning model that is considered to improve students' conceptual understanding is guided inquiry with mind map and cooperative type TGT. The purpose of this study is to see the effect of guided inquiry learning model with a mind map and cooperative type TGT on understanding students' concepts. The subjects in this study were seventh-grade students of SMPK St. Yoseph Noelbaki. The data of the research results were analyzed by analysis of one-way variance and descriptive. The results showed that there was an effect of the implementation of a guided inquiry learning model with mind map and cooperative TGT type on students' conceptual understanding, with a probability value (sig.) Of 0.01 smaller than the alpha value of 0.05.